The Effect of Using Homework Assignments on the Achievements of Elementary School Pupils in Tulkarm Governorate - Safwat Hesham Husne Abdel-Rahman (My University, 2011)
This study aims to exploring the effect of using homework on the Fourth grade students' achievement levels of the Elementary Schools in Tulkarm Governorate, and how the low levels of thinking in Bloom's Taxonomy (knowledge, comprehension ,and application), will be affected by homework. The problem of the study has been limited for to answering the following questions: 1.What is the effect of using homework on Fourth Grade students' achievement in Tulkarm Governorate? 2.What is the effect of using homework on students' achievement according to sex variable (males and females)? 3.What is the effect of using homework on students' achievement according to low levels of Bloom's Taxonomy (knowledge, understanding, application)? The population of the study included all Fourth Grades at government Schools in Tulkarm Governorate. A sample of (130) students (males and females) from the Fourth Grade from Bala' Boys' School and Bala' Girls' School in Tulkarm Governorate in the Second Semester (2009 - 2010). The sample was randomly chosen and divided into two groups: Experimental group, the males and females, were taken from sections (A) and for the control group the males and females, were taken from section (B). The experimental group consisted of sixty-five (65) male and female students. (Thirty males and thirty-five females), these students have been taught the learning material by using homework. The control group consisted of sixty-five (65) students, (Thirty males and thirty -five females), these students have been taught the material by using the traditional method without giving them homework. The achievement test was prepared after the preparation and reviewing the learning material. Six lessons from Arabic language syllabus were analyzed. This analysis includes aims, methods, specification table and homework which is prepared according to Bloom's low levels (knowledge, understanding and application). The teaching material, the homework and the achievement tests have been given the jury who are specialized and experienced to test the validity of the study instrument. The researcher has also used (Test- Retest Method) to calculate the stability of the test which was (0.96) and this is a good value that achieves the aims of the study. This study has been applied on the sample and the results of the achievement test have been treated by using statistical packages for the social science in order to identify the effect of using homework on the Fourth Grade students' achievement levels in the syllabus of the Arabic language according the low levels of Bloom's Taxonomy (knowledge, understanding, application). The results of study have shown that there is a significant success in the achievement post-test at the knowledge level, understanding level, and at the application level (according to Bloom's Taxonomy) in favor at the experimental group in the Arabic language, They have also shown that there is homogeneity between the males and females through the interaction between the teaching method and sex variable. In light of the study results, the research recommends that there is a necessity for using different kinds of homework according to Bloom's Taxonomy of low levels (knowledge, understanding, application) in teaching the basic stages in Tulkarm Governorate to increase the achievement levels. She also recommends and carrying out further studies to search more in homework and its efficiency

هدفت هذه الدراسة إلى التعرف على أثر استخدام الواجبات المنزلية في التحصيل لدى طلبة الصف الرابع الأساسي في مدارس محافظة طولكرم الحكومية، وفي أي من مستويات التفكير الدنيا(معرفة،فهم،تطبيق) سوف تؤثر هذه الواجبات المنزلية في تحصيل الطلبة،وحددت مشكلة الدراسة في صياغة أسئلة الدراسة التالية: 1. ما أثر استخدام الواجبات المنزلية في تحصيل طلبة الصف الرابع الأساسي في محافظة طولكرم؟ 2. ما أثر استخدام الواجبات المنزلية في تحصيل الطلبة حسب متغير الجنس؟ 3. ما أثر استخدام الواجبات المنزلية في تحصيل الطلبة في مستويات التفكير الدنيا لبلوم (معرفة، فهم، تطبيق)؟ وقد تكون مجتمع الدراسة من طلبة الصف الرابع الأساسي في مدارس محافظة طولكرم الحكومية، و تم اختبار فروض الدراسة عن طريق إجراء دراسة شبه تجريبية على عينة تألفت من ( 130 ) طالبًا وطالبة من طلبة الصف الرابع الأساسي في مدرسة ذكور بلعا الأساسية، 2010 ) بمحافظة طولكرم، - ومدرسة بنات بلعا الأساسية في الفصل الدراسي الثاني للعام 2009 وتم توزيع العينة إلى مجموعتين تجريبية وضابطة من شعب (أ،ب) ذكوراَ وإناثًا، وقد تكونت المجموعة التجريبية من ( 65 طالب وطالبة) منهم ( 30 ذكر و 35 أنثى) تعلموا المادة التعليمية باستخدام الواجبات المنزلية، وتكونت المجموعة الضابطة من 65 طالب وطالبة) منهم ( 30 ذكر و 35 أنثى) تعلموا المادة التعليمية بالطريقة التقليدية بدون الواجبات المنزلية. وتم إعداد أداة الدراسة المتمثلة بالاختبار التحصيلي بعد الاطلاع والتحضير التفصيلي للمادة التعليمية،وتحليل محتوى ستة دروس من مقرر اللغة العربية للصف الرابع الأساسي في الفصل الدراسي الثاني يشتمل على الأهداف والأساليب، وبناء جدول مواصفات، و إعداد واجبات منزلية حسب تصنيف بلوم تشمل الأهداف المعرفية الدنيا(المعرفة،الفهم،تطبيق)، وتم عرض المادة التعليمية والواجبات المنزلية واختبارات فحص التحصيل الدراسي على لجنة محكمين من ذوي الاختصاص والخبرة لتحقيق صدق أداة الدراسة، كما قامت الباحثة بحساب ثبات الاختبار،وبلغت قيمته ( 0.96 )، وهي قيمة عالية من الثبات تفي بأغراض الدراسة، وبعد تطبيق الدراسة على العينة تم معالجة نتائج الاختبار التحصيلي باستخدام برنامج الرزم بهدف التعرف على أثر استخدام الواجبات المنزلية في SPSS الإحصائية للعلوم الاجتماعية تحصيل طلاب الصف الرابع الأساسي في منهاج اللغة العربية حسب تصنيف مستويات بلوم المعرفية الدنيا معرفة،فهم، وتطبيق. وأظهرت نتائج الدراسة أن للواجبات المنزلية أثرًا في زيادة التحصيل لصالح المجموعة التجريبية في مادة اللغة العربية، وتفوقا حسب مستويات بلوم المعرفية الدنيا معرفة،فهم، تطبيق على الذكور والإناث على حد سواء بدون اختلاف حسب متغير الجنس. وعلى ضوء نتائج الدراسة الحالية وتفسيراتها توصي الدراسة بضرورة استخدام الواجبات المنزلية وتنوعها حسب مستويات بلوم المعرفية الدنيا (معرفة، فهم، تطبيق) في تدريس المرحلة الأساسية في محافظة طولكرم لزيادة التحصيل الدراسي، و إجراء المزيد من الدراسات التي تبحث في الواجبات المنزلية وفاعليتها.
أثر استخدام الواجبات المنزلية في تحصيل الطلاب للمرحلة الأساسية في محافظة طولكرم